Historic journey to the Philippines (Trilogy Multimedia, 1998)
Based on Pigafetta's diaries, the CD tells about Magellan's vogaye to the Philippines. It gives an overview of the route with descriptions of the ports,the islands and other locations; the forces of nature that he battled as he ventured into unexplored territories; and the significant characters encountered in the voyage